Preparation method of wear-resistant heat-conducting material and application of wear-resistant heat-conducting material in rear cover of mobile phone

By introducing bisphenol acid-based polystyrene and silicon carbide micropowder into polycarbonate materials, and performing surface modification and melt blending, the thermal conductivity and wear resistance of polycarbonate materials in mobile phone back cover applications is solved. The problem of insufficient results has achieved higher thermal conductivity and wear resistance.

CN119490732APending Publication Date: 2025-02-21DONGGUAN ZHENYU MOULD PLASTIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411642669.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Existing polycarbonate materials have problems with insufficient thermal conductivity and wear resistance in mobile phone back cover applications.

Method used

By introducing bisphenol acid-based polystyrene and silicon carbide micropowder into the polycarbonate, and surface modification and melt blending, a stable polycarbonate-polystyrene alloy system is formed to improve the thermal conductivity and resistance of the material. Abrasive.

Benefits of technology

It significantly improves the thermal conductivity and heat dissipation performance of the material, while enhancing the wear resistance of the material, reducing the mass loss rate, and is suitable for applications such as mobile phone back covers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of polycarbonate, and discloses a preparation method of a wear-resistant heat-conducting material and an application of the wear-resistant heat-conducting material in a rear cover of a mobile phone, N, N-dimethylformamide, silicon carbide micro powder and bisphenol ester acid polystyrene are added into a reaction container for surface modification, then the mixture and bisphenol A polycarbonate are subjected to melt extrusion and granulation, and the wear-resistant heat-conducting material is obtained. Bisphenol ester acid-based polystyrene contains carboxyl and can interact with hydroxyl on the surface of silicon carbide micro powder, surface modification of silicon carbide is achieved, dispersity of the silicon carbide micro powder in polycarbonate is improved, silicon carbide is evenly dispersed in polycarbonate, a continuous heat conduction channel is formed, and the heat conduction performance of the polycarbonate is improved. The heat conductivity coefficient and the heat conduction and heat dissipation performance of the material are remarkably improved, meanwhile, the mass loss rate of the material is reduced, and good wear resistance is shown. The method has good practical application in the aspects of mobile phone rear cover shells and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polycarbonate, in particular to a preparation method of a wear-resistant heat-conductive material and an application of the same in a mobile phone back cover. Background Art

[0002] Polycarbonate is a high molecular polymer containing carbonate groups in its molecular chain. Aromatic polycarbonate has good flame retardancy, high antioxidant properties, and excellent heat resistance. It is widely used in electronic and electrical fields such as mobile phone casings, packaging fields such as food and medicine, and construction fields such as hollow panels. Improving the thermal conductivity, heat dissipation, and wear resistance of polycarbonate will help expand its practical application in mobile phone casings, computer casings, etc.

[0003] By compounding polycarbonate with ABS, polystyrene, polylactic acid and other materials, an alloy material with better performance can be obtained. Patent application number CN118240356A discloses a PC / PS alloy composition and its preparation method and application. With polycarbonate, polystyrene, compatibilizer and toughening agent as raw materials, the obtained PC / PS alloy material has good flame retardancy, weld line strength and other properties. However, the patent requires the additional addition of compatibilizer, and the PC / PS alloy treatment does not show good wear resistance, thermal conductivity and heat dissipation and other properties.

[0004] Silicon carbide has high thermal conductivity, high strength, good wear resistance, and is widely used in polymer materials. It is usually necessary to modify the surface of silicon carbide to improve its compatibility in materials such as polycarbonate and improve its dispersibility. Summary of the invention

[0005] The technical problem solved by the invention is to provide a polycarbonate material with good wear resistance and high thermal conductivity, which can be applied to the back cover of a mobile phone.

[0006] The technical solution of the present invention is: a method for preparing a wear-resistant heat-conducting material:

[0007] Step S1: Add N,N-dimethylformamide, styrene, styrene-based bisphenol acid monomer, and azobisisobutyronitrile into a reaction container, carry out polymerization reaction at 70-80° C. in a nitrogen atmosphere for 18-24 hours, add ethanol to dilute, filter and then wash the filter cake with ethanol to obtain bisphenol acid-based polystyrene.

[0008] Step S2: Add N,N-dimethylformamide and 20-40 parts by weight of silicon carbide powder into a reaction container, add 5-18 parts by weight of bisphenol acid-based polystyrene after ultrasonic dispersion, stir at 60-75°C for surface modification for 3-6 hours, remove N,N-dimethylformamide by reduced pressure distillation, add the mixture and 100 parts by weight of bisphenol A polycarbonate into a twin-screw extruder after drying, the temperature of zones 1 to 4 is 260-280°C, the head temperature is 250-260°C, the screw speed is 400-500r / min, and granulation is performed after melt extrusion to obtain a wear-resistant heat-conductive material.

[0009] Furthermore, in step S1, the masses of the styrene-based bisphenol acid monomer and azobisisobutyronitrile are 5-20% and 0.4-0.5% of the mass of styrene.

[0010] Furthermore, the preparation method of styrene-based bisphenol acid monomer is as follows: add dichloromethane, bisphenol acid, 4-vinylbenzoyl chloride, and triethylamine to a reaction vessel in an ice bath, react at 20-25° C. for 6-10 hours, perform vacuum distillation, separate by silica gel column chromatography, and use ethyl acetate and petroleum ether solution as eluents to obtain styrene-based bisphenol acid monomer. The reaction formula is:

[0011]

[0012] Furthermore, the masses of 4-vinylbenzoyl chloride and triethylamine are 116-140% and 71-85% of the mass of diphenolic acid, respectively.

[0013] Furthermore, wear-resistant heat-conductive materials are used in the back cover of mobile phones.

[0014] The technical effect of the present invention is as follows: the present invention utilizes styrene and styrene-based bisphenol acid monomers for copolymerization to obtain bisphenol acid-based polystyrene containing carboxyl groups, then modifies the surface of silicon carbide micropowder, and finally melt-blends with bisphenol A polycarbonate to obtain a wear-resistant heat-conductive material.

[0015] The bisphenol acid-based polystyrene of the present invention contains a bisphenol ester-based structure, and bisphenol A polycarbonate also has a similar bisphenol carbonate structure. The two have similar compatibility, so that the polystyrene and the bisphenol A polycarbonate have good interface compatibility, and the two form a stable and compatible polycarbonate-polystyrene alloy system, which exhibits higher tensile strength and elongation at break.

[0016] The bisphenol acid-based polystyrene of the present invention contains carboxyl groups. During the modification process, the carboxyl groups can interact with the hydroxyl groups on the surface of the silicon carbide micropowder, thereby realizing the surface modification of the silicon carbide and improving the dispersibility of the silicon carbide micropowder in the polycarbonate. The silicon carbide has high wear resistance and thermal conductivity, is evenly dispersed in the polycarbonate, forms a continuous heat conduction path, significantly improves the thermal conductivity and thermal conductivity of the material, and reduces the mass loss rate of the material, showing good wear resistance. The obtained wear-resistant heat-conductive material has good practical applications in the rear cover shell of mobile phones and the like. DETAILED DESCRIPTION

[0017] In order to understand the technical features and contents of the present invention in detail, the preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described in the embodiments, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described here.

[0018] Example 1

[0019] (1) In an ice bath, 35 mL of dichloromethane, 2 g of diphenolic acid (CAS No. 126-00-1), 2.8 g of 4-vinylbenzoyl chloride (CAS No. 1565-41-9), and 1.7 g of triethylamine were added to a reaction container, and the mixture was reacted at 20° C. for 10 h. The mixture was distilled under reduced pressure and separated by silica gel column chromatography, using ethyl acetate and petroleum ether solution as eluents to obtain a styryl bisphenol acid monomer.

[0020] (2) Add 200 mL of N,N-dimethylformamide, 40 g of styrene, 2 g of styrene-based bisphenol acid monomer, and 0.16 g of azobisisobutyronitrile to a reaction container, perform a polymerization reaction at 75° C. in a nitrogen atmosphere for 18 h, add ethanol to dilute, filter, and then wash the filter cake with ethanol to obtain bisphenol acid-based polystyrene.

[0021] (3) 2L N,N-dimethylformamide and 200g silicon carbide powder (average particle size 2um) were added to the reaction container, and 50g bisphenol acid-based polystyrene was added after ultrasonic dispersion. The surface was modified by stirring at 75°C for 3h, and N,N-dimethylformamide was removed by vacuum distillation. After drying, the mixture and 1kg bisphenol A polycarbonate were added to a twin-screw extruder. The temperatures of zones 1 to 4 were 260°C, 270°C, 280°C, and 275°C, the head temperature was 250°C, the screw speed was 500r / min, and the melt was extruded and granulated to obtain a wear-resistant thermal conductive material.

[0022] Example 2

[0023] (1) In an ice bath, 25 mL of dichloromethane, 2 g of diphenolic acid, 2.32 g of 4-vinylbenzoyl chloride, and 1.42 g of triethylamine were added to a reaction container, and the mixture was reacted at 25° C. for 6 h. The mixture was distilled under reduced pressure and separated by silica gel column chromatography using ethyl acetate and petroleum ether solution as eluents to obtain styryl bisphenol acid monomer.

[0024] (2) Add 300 mL of N,N-dimethylformamide, 40 g of styrene, 5 g of styrene-based bisphenol acid monomer, and 0.18 g of azobisisobutyronitrile into a reaction container, perform polymerization at 70° C. in a nitrogen atmosphere for 24 h, add ethanol to dilute, filter, and then wash the filter cake with ethanol to obtain bisphenol acid-based polystyrene.

[0025] (3) Add 2.5L N,N-dimethylformamide and 300g silicon carbide powder (average particle size 2um) into a reaction container, add 120g bisphenol acid-based polystyrene after ultrasonic dispersion, stir at 75°C for surface modification for 5h, remove N,N-dimethylformamide by vacuum distillation, and add the mixture and 1kg bisphenol A polycarbonate into a twin-screw extruder after drying. The temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 260°C, the screw speed is 400r / min, and granulation is performed after melt extrusion to obtain a wear-resistant thermal conductive material.

[0026] Example 3

[0027] (1) 300 mL of N,N-dimethylformamide, 40 g of styrene, 8 g of styrene-based bisphenol acid monomer (prepared in Example 1), and 0.2 g of azobisisobutyronitrile were added to a reaction container, and polymerization was carried out at 80° C. for 18 h in a nitrogen atmosphere. Ethanol was added for dilution, and the filter cake was washed with ethanol after suction filtration to obtain bisphenol acid-based polystyrene.

[0028] (2) 3L N,N-dimethylformamide and 400g silicon carbide powder (average particle size 2um) were added to a reaction container, and 180g bisphenol acid-based polystyrene was added after ultrasonic dispersion. The mixture was stirred at 60°C for surface modification for 6h, and N,N-dimethylformamide was removed by vacuum distillation. After drying, the mixture and 1kg bisphenol A polycarbonate were added to a twin-screw extruder. The temperatures of zones 1 to 4 were 260°C, 270°C, 280°C, and 275°C, the die temperature was 250°C, the screw speed was 500r / min, and the melt was extruded and granulated to obtain a wear-resistant thermal conductive material.

[0029] Comparative Example 1

[0030] (1) 1 kg of bisphenol A polycarbonate was added into a twin-screw extruder, the temperatures of zones 1 to 4 were 260° C., 270° C., 280° C., and 275° C., the die temperature was 250° C., the screw speed was 500 r / min, and the polycarbonate material was obtained by granulation after melt extrusion.

[0031] Comparative Example 2

[0032] (1) 200 g of silicon carbide powder (average particle size 2 μm) and 1 kg of bisphenol A polycarbonate were added to a twin-screw extruder. The temperatures of zones 1 to 4 were 260° C., 270° C., 280° C., and 275° C., the die temperature was 250° C., and the screw speed was 500 r / min. After melt extrusion, granulation was performed to obtain a wear-resistant heat-conductive material.

[0033] Comparative Example 3

[0034] (1) 50 g of bisphenol acid-based polystyrene and 1 kg of bisphenol A polycarbonate were added to a twin-screw extruder, the temperatures of zones 1 to 4 were 260° C., 270° C., 280° C., and 275° C., the die temperature was 250° C., the screw speed was 500 r / min, and the melt was extruded and pelletized to obtain a wear-resistant thermal conductive material.

[0035] Comparative Example 4

[0036] (1) Add 200 mL of N,N-dimethylformamide, 40 g of styrene, 2 g of divinylbenzene, and 0.16 g of azobisisobutyronitrile to a reaction container, carry out polymerization reaction at 75° C. in a nitrogen atmosphere for 18 h, add ethanol to dilute, filter, and wash the filter cake with ethanol to obtain a polystyrene copolymer.

[0037] (2) Add 2L N,N-dimethylformamide and 200g silicon carbide powder (average particle size 2um) into a reaction container, add 50g polystyrene copolymer after ultrasonic dispersion, stir at 75°C for surface modification for 3h, remove N,N-dimethylformamide by vacuum distillation, add the mixture and 1kg bisphenol A polycarbonate into a twin-screw extruder after drying, the temperatures of zones 1 to 4 are 260°C, 270°C, 280°C, and 275°C, the head temperature is 250°C, the screw speed is 500r / min, and granulation is performed after melt extrusion to obtain a wear-resistant thermal conductive material.

[0038] The wear-resistant heat-conductive material is injected into a specimen by an injection molding machine. The tensile properties are tested according to GB / T 1040.1-2018 standard.

[0039] The thermal conductivity was tested by a thermal conductivity tester using a steady-state method, and the sample was a circular sample with a radius of 6 cm.

[0040] The wear resistance of the wear-resistant thermal conductive material was tested using a friction and wear testing machine. The wear part was a 45# steel ring. The load was 19.6N and the speed was 200r / min. After the test, the mass m of the wear-resistant thermal conductive material test block before and after wear was weighed. 前 and m 后 , measure the test block width L and wear scar width d, and calculate the mass loss rate S.

[0041] S=(m 前 -m 后 ) / (L×d).

[0042] Table 1 Wear-resistant thermal conductive material performance test

[0043]

[0044] As shown in Table 1, in Examples 1-3, the surface of silicon carbide powder was modified by using bisphenol acid-based polystyrene, and then melt-blended with bisphenol A polycarbonate. The wear-resistant thermal conductive material obtained has high tensile strength and elongation at break, good mechanical properties, low mass loss rate, high thermal conductivity, and good thermal conductivity and heat dissipation performance. This is because the bisphenol acid-based polystyrene contains a bisphenol ester structure. Bisphenol A polycarbonate also has a similar bisphenol carbonate structure. The two have similar compatibility, so that there is good interface compatibility between polystyrene and bisphenol A polycarbonate, and the two form a stable and compatible polycarbonate-polystyrene alloy system, showing higher tensile strength and elongation at break. At the same time, bisphenol acid-based polystyrene contains carboxyl groups. During the modification process, the carboxyl groups can interact with the hydroxyl groups on the surface of silicon carbide micropowder, thereby realizing surface modification of silicon carbide and improving the dispersibility of silicon carbide micropowder in polycarbonate. Silicon carbide has high wear resistance and thermal conductivity, and is evenly dispersed in polycarbonate to form a continuous heat conduction path, which significantly improves the thermal conductivity and thermal conductivity and heat dissipation performance of the material, while reducing the mass loss rate of the material and showing good wear resistance.

[0045] Comparative Example 1 does not add bisphenol acid-based polystyrene and silicon carbide powder, and the tensile strength, elongation at break and thermal conductivity of the polycarbonate material are low, and the mass loss rate and wear resistance are poor.

[0046] In Comparative Example 2, only silicon carbide powder is added. Due to the poor compatibility and dispersibility between silicon carbide powder and bisphenol A polycarbonate, it is difficult to form a continuous heat conduction path, resulting in the thermal conductivity of the material being lower than that of the embodiments, and the mass loss rate is large and the wear resistance is poor.

[0047] In Comparative Example 3, only bisphenol acid-based polystyrene is added, which can form a stable and compatible alloy system with bisphenol A polycarbonate. The tensile strength and elongation at break of the material are higher than those of Comparative Example 1. However, silicon carbide micropowder is not added, the thermal conductivity of the material is low, the mass loss rate is large, and the thermal conductivity and wear resistance are poor.

[0048] Comparative Example 4 uses common divinylbenzene instead of the styrene-based bisphenol acid monomer. The obtained polystyrene copolymer does not contain a bisphenol ester structure, has poor compatibility with bisphenol A polycarbonate, and does not contain a carboxyl group. It cannot interact with the surface of the silicon carbide micropowder and cannot achieve surface modification of the silicon carbide micropowder, resulting in poor compatibility and dispersibility of the silicon carbide micropowder in the polycarbonate, making it difficult to form a continuous heat conduction path in the material matrix, resulting in the thermal conductivity of the material being lower than that of the various embodiments, and a large mass loss rate and poor wear resistance.

[0049] The above describes some embodiments of the present invention, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a wear-resistant heat-conductive material, characterized in that: The preparation method comprises the following steps: Step S1: Add N,N-dimethylformamide, styrene, styrene-based bisphenol acid monomer, and azobisisobutyronitrile into a reaction container, perform polymerization reaction in a nitrogen atmosphere, add ethanol to dilute, and wash the filter cake with ethanol after suction filtration to obtain bisphenol acid-based polystyrene; Step S2: Add N,N-dimethylformamide and 20-40 parts by weight of silicon carbide powder into a reaction container, add 5-18 parts by weight of bisphenol acid-based polystyrene after ultrasonic dispersion, perform surface modification, remove N,N-dimethylformamide by vacuum distillation, add the mixture and 100 parts by weight of bisphenol A polycarbonate into a twin-screw extruder after drying, melt-extrude and granulate to obtain a wear-resistant thermal conductive material.

2. The method for preparing the wear-resistant heat-conductive material according to claim 1, characterized in that: In the step S1, the mass of the styrene-based bisphenol acid monomer and azobisisobutyronitrile is 5-20% and 0.4-0.5% of the mass of styrene.

3. The method for preparing the wear-resistant heat-conductive material according to claim 1, characterized in that: The polymerization reaction in step S1 is carried out at 70-80° C. for 18-24 hours.

4. The method for preparing the wear-resistant heat-conductive material according to claim 1, characterized in that: In the step S2, the surface modification is carried out by stirring at 60-75° C. for 3-6 hours.

5. The method for preparing the wear-resistant heat-conductive material according to claim 1, characterized in that: In step S2, the temperature of zones 1 to 4 of the twin-screw extruder is 260-280° C., the die head temperature is 250-260° C., and the screw speed is 400-500 r / min.

6. The method for preparing the wear-resistant heat-conductive material according to claim 1, characterized in that: The preparation method of the styrene-based bisphenol acid monomer comprises the following steps: adding dichloromethane, bisphenol acid, 4-vinylbenzoyl chloride and triethylamine into a reaction container in an ice bath, performing reduced pressure distillation after the reaction, performing silica gel column chromatography separation, and using ethyl acetate and petroleum ether solution as eluents to obtain the styrene-based bisphenol acid monomer.

7. The method for preparing the wear-resistant heat-conductive material according to claim 6, characterized in that: The masses of the 4-vinylbenzoyl chloride and triethylamine are 116-140% and 71-85% of the mass of the diphenolic acid respectively.

8. The method for preparing the wear-resistant heat-conductive material according to claim 6, characterized in that: The reaction is carried out at 20-25°C for 6-10 h.

9. Use of the wear-resistant heat-conductive material obtained by the preparation method according to any one of claims 1 to 8 in a mobile phone back cover.

Citation Information

Patent Citations

  • PC / PS alloy composition and preparation method and application thereof

    CN118240356A